THE PERFORNIANCE OF PBAHJRXS FED D11ETS CONTAINING WATER WIYACINTX-3 (Eichlnonlia Grassiyes) LEAF MEAX, - DAIRO, F.A.S. (Nigerian Journal of Animal Science, 2023)
Thirty-two crossbred wearier rabbits (New Zealand White x California White) with an initial weight that ranged between 0.M and 0.94kg at 8 weeks old were randomly allotted to 4 experimental dietary treatments in which water hyacinth leaf meal (WIIIM) replaced maize at 0,5,10 and 15%) inclusion levels. The average feed consumed, feed conversion ratio, operative protein efficiency ratio and crude fiber (CF) rekelrtiol were significantly influenced (Pc0.05). The body weight gain, dry matter (DM) and the nitrogen retention were not affected significantly. There were no sex and treatment interaction on all the parameters monitored. The coefficient of determination R2, for the average feed consumed, DM and CF retention were 0.77, 0.83 and 0.84 respectively. Water hyacinth can replace maize at 15% inclusion level without adverse effects on the rabbit performance.